Інтерпретаційні парадокси текстової відкритості: наратологічне, психоаналітичне та феміністичне розкодування новели «Грішниця» Леся Мартовича - Лепьохін, Є. (Слово і Час, 2022)
Пропонована стаття розгортає можливі інтерпретаційні фокуси для
вивчення тем «комунікації» та «порозуміння» поміж статями, взаємостосунків чоловіка і жінки у новелі «Грішниця» (1904) Леся Мартовича (1871—1916). Ці явища досліджуються за допомогою наратологічних, психоаналітичних та феміністичних методологічних стратегій, з
урахуванням тенденцій текстуальної відкритості та рецептивної парадоксальності. Інтерпретація психологічних портретів персонажів відбувається у векторах поліфонічного текстуального простору реальності,
яка, з одного боку, наснажена ідеологією патріархальності, а з іншого, —
емансипованості жінки. The scholarly debate over the writer’s outlook and individual literary style of Les Martovych
(1871—1916) is still relevant. The ironic mood of his works and its genesis, the psychological
and cultural foundation of his writings, the vision of Martovych’s narration in the context of
examining his psychological ground – this is what modern researchers, in particular, Roman
Pikhmanets, Olena Hnidan, Oleh Ilnytskyi, and Hanna Marchuk, most oft en reflected on.
Just as topical is the interpretation of the compositional and semantic level of the writer’s
texts along with the study of the peculiarities of using linguistic and stylistic means for the
realization of the author’s intention in the translations of his works into foreign languages.
This paper focuses on the man-woman relationship in the short story “The Sinner”
(1904) in terms of post-structural psychoanalytic, narratological, and feminist perspectives.
Obvious is the gap between the notion of a woman as a feminine character and as a sociohistorical
subject in a patriarchal world. The interpretation of the psychological portraits
of the characters strives for defining the elusive nature of a reality that is driven by the
ideology of patriarchy on the one hand, and the emancipation of women on the other.
Using the method of ‘suture’, the paper demonstrates the process of creating female and male
subjectivity at the level of narrative discourse.
The findings may serve those who research the Ukrainian literary trends of the late 19th —
early 20th centuries, peculiarities of the development of Ukrainian prose of the mentioned
period in relation to the general European context, feminist-psychoanalytic discourse in
literature, and the mechanisms of creating female and male images in prose works.